The extragradient method for quasi-monotone variational inequalities. (2nd September 2022) - Salahuddin
ABSTRACT: The goal of this paper is to study quasi-monotone variational inequality problems in infinite dimensional Hilbert spaces and to prove that the iterative sequence generated by an extragradient algorithm converges weakly to a solution.